Balancing paid work and personal life coping mechanisms of men and women in the academe - Samson-Quintillan, Lynette (Philippine Journal of Labor and Industrial Relations, 2010)
This case study delves on gender differences in coping mechanisms to achieve paid work (PW) and personal life (PL) balance. It involves 145 men and 205 women employees of the University of the Philippines (UP) Diliman. It aims to identify coping mechanisms adopted by UP Diliman workers, their PW-PL issues and concerns, and factors that affect their manner of coping. Using a triangulated approach involving organisational ethnography and survey method, minimal gender differences are observed. Results likewise reveal gender differentials in terms of PW-PL issues and concerns, time management and spending habits, values and goals in life, and views about coping, the importance of PW-PL balance role of the workers union, and UP's HR-related policies.